Incremental value of cystatin C over conventional renal metrics for predicting clinical response and outcomes in cardiac resynchronization therapy: The BIOCRT study. (15th February 2016) - Chatterjee, Neal A.; Singh, Jagmeet P.; Szymonifka, Jackie; Deaño, Roderick C.; Thai, Wai-ee; Wai, Bryan; Min, James K.; Januzzi, James L.; Truong, Quynh A.
Abstract: Background: Despite the benefit of CRT in select patients with heart failure (HF), there remains significant need for predicting those at risk for adverse outcomes for this effective but costly therapy. CysC, an emerging marker of renal function, is predictive of worsening symptoms and mortality in patients with HF. This study assessed the utility of baseline and serial measures of cystatin C (CysC), compared to conventional creatinine-based measures of renal function (estimated glomerular filtration rate, eGFR), in predicting clinical outcomes following cardiac resynchronization therapy (CRT). Methods: In 133 patients, we measured peripheral venous (PV) and coronary sinus (CS) CysC concentrations and peripheral creatinine levels at the time of CRT implant. Study endpoints included clinical response to CRT at 6 months and major adverse cardiac events (MACE) at 2 years. Results: While all 3 renal metrics were predictive of MACE (all adjusted p ≤ 0.02), only CysC was associated with CRT non-response at 6 months (adjusted odds ratio 3.6, p = 0.02). CysC improved prediction of CRT non-response (p ≤ 0.003) in net reclassification index analysis compared to models utilizing standard renal metrics. Serial CysC > 1 mg/L was associated with 6-month CRT non-response and reduced 6-minute walk distance as well as 2-year MACE (all p ≤ 0.04). Conclusion: In patients undergoing CRT, CysC demonstrated incremental benefit in the prediction of CRT non-response when compared to standard metrics of renal function. Baseline and serial measures of elevated CysC were predictive of CRT non-response and functional status at 6 months as well as long-term clinical outcomes.